A surgical procedure for re-implanting a tooth that has been rendered hopeless because of periodontitis: a case report - Singh, Gaurav; Chauhan, Shailendra S; Nagpal, Ajay; Sinha, Aditya; Sharma, Satendra; Kulshrestha, Saksham (Archives of Surgery and Clinical Research, 2022)
Aim and methodology: This article describes a periodontally compromised, hopeless incisor tooth that was purposefully replanted, along with the results after six months. This entails the deliberate removal of the tooth and its subsequent correct manipulation and endodontic restoration before reinserting it into the socket. Results: Hopeless lower incisors with periodontal involvement were transplanted utilizing an implant surgical drilling approach after receiving root canal therapy and tetracycline-HCI conditioning. Bone graft material was added and the procedure was monitored for six months. The tooth was observed to be asymptomatic, functioning normally, and showing no pathologic radiological changes. With minimal bleeding during probing and no growth of pathological pockets, the periodontal condition was within normal limits. Alveolar bone support was seen to be adequate. The results may suggest that, in some circumstances, purposeful replantation is a viable strategy of treatment for maintaining native dentition. Conclusion: Intentional tooth reimplantation can be an alternative treatment option for periodontally involved teeth with poor or hopeless prognoses.